2017
DOI: 10.1038/srep46535
|View full text |Cite
|
Sign up to set email alerts
|

Normally lethal amino acid substitutions suppress an ultramutator DNA Polymerase δ variant

Abstract: In yeast, the pol3-01,L612M double mutant allele, which causes defects in DNA polymerase delta (Pol δ) proofreading (pol3-01) and nucleotide selectivity (pol3-L612M), confers an “ultramutator” phenotype that rapidly drives extinction of haploid and diploid MMR-proficient cells. Here, we investigate antimutator mutations that encode amino acid substitutions in Pol δ that suppress this lethal phenotype. We find that most of the antimutator mutations individually suppress the pol3-01 and pol3-L612M mutator phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…These could conceivably include suppressor mutations functioning to restrain elevated mutation rates ( Morrison and Sugino, 1994 ; Herr et al, 2011a ; Williams et al, 2013 ). Importantly, no additional mutations in POLE were sequenced, suggesting that viability of this cell line is not due to an acquired mutation elsewhere in POLE acting to suppress the mutation rate, as occurs frequently in yeast ( Herr et al, 2011a ; Williams et al, 2013 ; Herr et al, 2011b ; Dennis et al, 2017 ). While we cannot formally exclude the possibility that a de novo mutation in another gene acted to suppress the mutation rate in trans, no obvious candidates were identified.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These could conceivably include suppressor mutations functioning to restrain elevated mutation rates ( Morrison and Sugino, 1994 ; Herr et al, 2011a ; Williams et al, 2013 ). Importantly, no additional mutations in POLE were sequenced, suggesting that viability of this cell line is not due to an acquired mutation elsewhere in POLE acting to suppress the mutation rate, as occurs frequently in yeast ( Herr et al, 2011a ; Williams et al, 2013 ; Herr et al, 2011b ; Dennis et al, 2017 ). While we cannot formally exclude the possibility that a de novo mutation in another gene acted to suppress the mutation rate in trans, no obvious candidates were identified.…”
Section: Discussionmentioning
confidence: 96%
“…However, a number of direct biochemical comparisons of activity and fidelity ( Figure 1C , ( Shinbrot et al, 2014 ; Shlien et al, 2015 ) and unpublished observations) between several cancer mutant constructs and the D275A/E277A construct have not yet shown any significant differences that could account for this. Certain DNA Pol mutants, including some found in human tumors, can cause increased mutagenesis by inducing expansions of normal dNTP pools in yeast and human cells ( Dennis et al, 2017 ; Mertz et al, 2015 ; Williams et al, 2015 ). Interestingly, the pol2-4 allele has no effect on dNTP pools in yeast, suggesting a possible explanation for possible allelic differences with functional MMR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in yeast have shown that mutation rates are elevated in haploid and diploid strains carrying mutant Pol ε alleles that cause inactivated exonuclease activity (Morrison et al, 1991(Morrison et al, , 1993Morrison and Sugino, 1994;Ohya et al, 2002;Shcherbakova and Pavlov, 1996;Tran et al, 1999). As mutation rates increase, cells can adapt by evolving ways of suppressing this mutagenesis (Dennis et al, 2017;Herr et al, 2011b;Williams et al, 2013). Murine models have similarly shown that inactivation of Pol ε or d proofreading elevates mutation rates and accelerates cancer mortality (Albertson et al, 2009;Goldsby et al, 2002;Goldsby et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…All 8 strain sets acquired multiple pol3 mutations prior to their divergence (Fig 4C,D). Many mutations affect the same amino acid residue or are identical to known antimutator mutations ( A704V(2x), A786V, A677T, D831A, R475S, R815C ) [15,17,28]. Polδ plays an essential role in DNA replication.…”
Section: Resultsmentioning
confidence: 99%